2020
DOI: 10.1016/j.csbj.2020.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Structural change of retinoic-acid receptor-related orphan receptor induced by binding of inverse-agonist: Molecular dynamics and ab initio molecular orbital simulations

Abstract: Graphical abstract Conformational change of His479 side chain in the inverse-agonist-bound RORγt+3SX; (a) at 228 ns and (b) at 230 ns of MD simulations. By the rotation of His side chain, the interactions between His479 and 3SX/Tyr502 are significantly changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…In the event, adding a chlorine atom to compound 3 in the para position resulted in compound 4 , which inhibited IL-17 secretion from hPBMCs with a half-maximal inhibitory concentration (IC 50 ) of 70.7 nM. Similar dramatic shifts in activity have been described by other researchers, and a detailed molecular dynamics study of these observation has recently been reported . Further optimization of the scaffold is described below.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In the event, adding a chlorine atom to compound 3 in the para position resulted in compound 4 , which inhibited IL-17 secretion from hPBMCs with a half-maximal inhibitory concentration (IC 50 ) of 70.7 nM. Similar dramatic shifts in activity have been described by other researchers, and a detailed molecular dynamics study of these observation has recently been reported . Further optimization of the scaffold is described below.…”
Section: Resultssupporting
confidence: 63%
“…Similar dramatic shifts in activity have been described by other researchers, and a detailed molecular dynamics study of these observation has recently been reported. 22 Further optimization of the scaffold is described below.…”
Section: ■ Resultsmentioning
confidence: 99%
“…We and newly calculated and collected more than 13 600 FMO calculation data sets ,, including data sets for 1418 unique PDB entries in collaboration with the FMO Drug Design Consortium (FMODD), which was established for the application of computational science such as FMO calculation to drug discovery. Using these data, we constructed the FMODB, which is a treasure trove of quantitative inter- and intramolecular interaction energies in biomolecular systems that will be useful for a wide range of applications in many life science research fields related to drug discovery and structural biology, including the study of molecular recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations that stand on the static crystal structure can predict atomic-level motion and capture the dynamic information of conformational transitions [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] . As a result of computation and algorithmic promotion, MD simulations have become an important source of complementary information in crystallography and a primary tool for mechanism research [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] .…”
Section: Introductionmentioning
confidence: 99%